Mixed culture (shrimps, oysters and macroalgae) to improve the productivity, and reduce the environmental impact to coastal ecosystem caused by shrimp hatcheries in Mexico - Guillermo Galindo Reyes (African Journal of Environmental Economics and Management, 2013)
In Mexico, shrimp hatcheries have been developed as intensive monocultures, resulting in hatcheries management troubles, economic losses and environmental impact. Therefore, the aim of this work was compare to a traditional culture vs. a mixed culture. Shrimp juveniles were distributed in aquariums and ponds at the same density (51 shrimps/m2) but ponds, also had oysters and macroalgae. Shrimps in aquaria and ponds were feed with same food amount. Water was change each two days, but in ponds only 20%. To compare traditional vs. mixed culture, shrimp’s growth, feed efficiency conversion and nutrients concentration, in aquariums and ponds were recorded. At experiment’s end, shrimps grew 35% more in ponds than aquariums; feed efficiency conversion was 0.68 units lower in ponds than aquariums, and NH4 concentrations were close to 3 and 1 mg/L in aquariums and ponds respectively. The mean increase weight in oyster and macroalgae, was 4.04 and 19.3 g respectively. Therefore, mixed culture has many ecological and economic advantages over traditional culture. Therefore it is suggested that scaling this technology to commercial level, in addition to shrimps, oysters and macroalgae are produced, which could be used for human consumption and animal fodder respectively. Also, this model improves water quality and reduces the environmental impact.